Correlation between Administering Misoprostol Vaginal and Intravenous Oxytocin with Successful Delivery - Dewi Aprilya Azka; Farianingsih; Homsiatur Rohmatin; Iit Emawati (KHD Production, 2023)
Labor induction is the stimulation of labor before there are signs of spontaneous labor. Induction of labor is performed if the risks of waiting for spontaneous delivery are judged to outweigh the risks of shortening the duration of pregnancy. Several labor induction methods are recommended, namely pharmacological and mechanical or non-pharmacological. Pharmacological induction is induction by administering prostaglandin E¹ analogs, namely misoprostol, and oxytocin, which will affect uterine contraction. This study aims to determine the relationship between vaginal administration of misoprostol and intravenous oxytocin with successful delivery. This research uses observational analytics with a cross-sectional approach. Sampling used the accidental sampling method with a sample of 32 respondents, which was carried out in August 2022. The instrument used for data collection was an observation sheet. The results showed that of the 32 respondents for successful delivery, almost all experienced successful delivery, with 24 respondents (75%). Multivariate data processing using the Spearman Rank test calculated using SPSS obtained a p-value < α = 0.001 (value α = 0.05). It can be concluded that H1 is accepted, which means there is a relationship between the vaginal administration of misoprostol and intravenous oxytocin with successful delivery in pregnant women.